A preclinical model of peripheral T‐cell lymphoma GATA3 reveals DNA damage response pathway vulnerability. Issue 6 (5th May 2022) - Kuczynski, Elizabeth A; Morlino, Giulia; Peter, Alison; Coenen‐Stass, Anna M L; Moss, Jennifer I; Wali, Neha; Delpuech, Oona; Reddy, Avinash; Solanki, Anisha; Sinclair, Charles; Calado, Dinis P; Carnevalli, Larissa S
Abstract: Peripheral T‐cell lymphoma (PTCL) represents a rare group of heterogeneous diseases in urgent need of effective treatments. A scarcity of disease‐relevant preclinical models hinders research advances. Here, we isolated a novel mouse (m)PTCL by serially transplanting a lymphoma from a germinal center B‐cell hyperplasia model ( Cγ1 ‐Cre Blimp1 fl/fl ) through immune‐competent mice. Lymphoma cells were identified as clonal TCRβ+ T‐helper cells expressing T‐follicular helper markers. We also observed coincident B‐cell activation and development of a de novo B‐cell lymphoma in the model, reminiscent of B‐cell activation/lymphomagenesis found in human PTCL. Molecular profiling linked the mPTCL to the high‐risk "GATA3" subtype of PTCL, showing GATA3 and Th2 gene expression, PI3K/mTOR pathway enrichment, hyperactivated MYC, and genome instability. Exome sequencing identified a human‐relevant oncogenic β‐catenin mutation possibly involved in T‐cell lymphomagenesis. Prolonged treatment responses were achieved in vivo by targeting ATR in the DNA damage response (DDR), a result corroborated in PTCL cell lines. This work provides mechanistic insight into the molecular and immunological drivers of T‐cell lymphomagenesis and proposes DDR inhibition as an effective and readily translatable therapy in PTCL. SYNOPSIS: A murine peripheral T‐cell lymphoma (mPTCL) arose coincident to B‐cell hyperplasia and was developed into a transplantable preclinical model. mPTCL and human PTCL lines responded to ATR inhibition, providing a rationale for clinical exploration of DNA‐damage response inhibitors for PTCL treatment. A transplantable lymphoma arose in a Cγ1 ‐Cre Blimp1 fl/fl mouse strain that is predisposed to spontaneous B‐cell hyperplasia. The lymphoma originated from a T‐cell progenitor and modelled cellular phenotypic hallmarks of human PTCL‐GATA3. A subset of human PTCL has activating mutations in β‐catenin. Similarly, a clonal Ctnnb1 1004A>C mutation encoding a K335T substitution in β‐catenin was found to have arisen spontaneously in the mouse lymphoma. mPTCL exhibited upregulation of β‐catenin and the downstream target Myc, together with biomarkers of DNA replication stress, and responded to the ATR inhibitor ceralasertib in vivo . Ceralasertib reduced proliferation of human PTCL cell lines, supporting a rationale for future clinical exploration of ATR inhibitors for the treatment of PTCL patients. Abstract : A murine peripheral T‐cell lymphoma (mPTCL) arose coincident to B‐cell hyperplasia and was developed into a transplantable preclinical model. mPTCL and human PTCL lines responded to ATR inhibition, providing a rationale for clinical exploration of DNA‐damage response inhibitors for PTCL treatment.